Systematic Literatur Review : Manfaat E-LKPD Berbasis Pendidikan Matematika Realistik Indonesia terhadap Kemampuan Pemecahan Masalah Pada Siswa SMP - Silvia Putri; Rani Refianti; Drajat Friansah (Prosiding Silampari Conference of Life Sciences and Techonology (Silamparilist), 2026)
The purpose of this research is to investigate and consolidate earlier work concerning the impact of Electronic Student Worksheets (E-LKPD) based on Indonesian Realistic Mathematics Education (PMRI) on enhancing the mathematical problem-solving abilities of junior high school students, specifically regarding Flat-Sided Three-Dimensional Figures. This study utilized a Systematic Literature Review (SLR) approach following the PRISMA 2020 framework. The methodology included creating research questions, setting selection criteria, designing a search strategy, choosing relevant studies, evaluating their quality, and synthesizing the results. A literature search was performed using Google Scholar, recognized national journals, and university repositories, focusing on works published between 2021 and 2025 with keywords such as E-LKPD, PMRI, Realistic Mathematics Education (RME), and mathematical problem-solving skills. The initial search yielded 35 articles. Following the screening, eligibility check, and quality review processes, 8 articles were identified as meeting the specified criteria and were selected for the final analysis. The results suggest that PMRI-based E-LKPD has a beneficial effect on students' problem-solving abilities in mathematics by offering contextual learning experiences that boost motivation and engagement, facilitating student-driven learning, and assisting students in relating mathematical ideas to real-world scenarios. Additionally, PMRI-based E-LKPD features realistic contexts, interactive digital elements, and incorporates problem-solving tasks aligned with Polya’s stages. The studies reviewed consistently highlighted the success of PMRI-based E-LKPD, with N-Gain scores reported between 0. 63 and a high classification, along with classical completion rates ranging from 78% to 86%. Hence, PMRI-based E-LKPD can be regarded as an effective and creative educational resource for enhancing junior high school students' mathematical problem-solving skills.